2023
DOI: 10.1073/pnas.2212776120
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cortical dynamics from the first years to the golden years

Abstract: In the largest and most expansive lifespan magnetoencephalography (MEG) study to date (n = 434, 6 to 84 y), we provide critical data on the normative trajectory of resting-state spontaneous activity and its temporal dynamics. We perform cutting-edge analyses to examine age and sex effects on whole-brain, spatially-resolved relative and absolute power maps, and find significant age effects in all spectral bands in both types of maps. Specifically, lower frequencies showed a negative correlation with age, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Another limitation of the current work is the absence of age matching between the SCD and MCI groups. While this is an inherent property of the cohort, due to the later occurrence of MCI in the Alzheimer’s continuum ( Bessi et al, 2018 , Smailovic et al, 2019 ), the different ages of the two groups may enhance some of the effects found in the identified markers ( Rempe et al, 2023 , Zappasodi et al, 2015 ). However, the differences found between SCD and MCI in microstate C duration and occurrence have an opposite sign compared to the age-related differences in the available literature ( Koenig et al, 2002 ), corroborating our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the current work is the absence of age matching between the SCD and MCI groups. While this is an inherent property of the cohort, due to the later occurrence of MCI in the Alzheimer’s continuum ( Bessi et al, 2018 , Smailovic et al, 2019 ), the different ages of the two groups may enhance some of the effects found in the identified markers ( Rempe et al, 2023 , Zappasodi et al, 2015 ). However, the differences found between SCD and MCI in microstate C duration and occurrence have an opposite sign compared to the age-related differences in the available literature ( Koenig et al, 2002 ), corroborating our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering prior literature indicating that the effects of age and cognitive ability on PAF are likely nonlinear (Dickinson et al, 2022; Rempe et al, 2023) and that these relations differ based on the diagnostic group (Dickinson et al, 2018; Dickinson et al, 2022; Edgar et al, 2015; Edgar et al, 2019), a generalized additive model (GAM; Hastie & Tibshirani, 1990) was fit using the mcgv package in R (Wood, 2011) to assess the joint effect of age, cognitive ability, and diagnostic status on PAF. In contrast to linear regression which estimates constant regression coefficients (β coefficients) for effects of interest, GAMs allow for more flexible modeling and detection of nonlinear effects by estimating smooth basis functions for predictors interest.…”
Section: Methodsmentioning
confidence: 99%
“…As such, alpha band activity provides a physiological index of neural and cognitive development (Grandy et al, 2013; Klimesch, 1999). Studies examining the developmental profile of alpha band activity have indicated age‐related increases in relative alpha power (defined as total alpha power divided by sum of power across all frequency bands) throughout childhood that are particularly pronounced in posterior regions of the brain (Cragg et al, 2011; Gasser et al, 1988; Rempe et al, 2023). Further, several studies have shown a significant positive correlation between relative alpha power and performance on standardized measures of intelligence (Fonseca et al, 2006; Schmid et al, 2002), a relationship presumed to reflect the overall increases in cognitive sophistication that take place during maturation (Klimesch, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to electroencephalography (EEG), MEG is less sensitive to conductivity differences between the brain, cerebral spinal fluid, skull, and scalp, and thus MEG is often preferred for source localization (Chen et al, 2019; Hämäläinen et al, 1993). For recent discussions on the use of MEG and source localization to study RS activity in children, see Ott et al (2021) and Rempe et al (2023).…”
Section: Introductionmentioning
confidence: 99%